Anatomical and Biochemical Pathogenesis of Motor Pathway Disruption in Cerebral Palsy: A Narrative Review - Mukhtar, Siti Fatimah; Ahmad, Asma Hayati; Mohd Ismail, Zul Izhar; Simok, Anna Alicia; Abdullah, Jafri Malin (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Cerebral palsy (CP) is a neurodevelopmental disorder characterized by motor impairments caused by brain lesions that affect motor pathways. Objective: This review describes the complex interaction between the thalamus and cerebral cortex in CP, the understanding of which would explain its pathophysiology and treatment strategies. Discussion: Cerebral palsy classification is based on motor impairment presentation, each with specific neurological deficits related to the disruption of specific motor pathways. The thalamus serves as a crucial relay station in these pathways, transmitting ascending and descending signals to the cortex via thalamocortical and corticothalamic tracts. Brain injuries like periventricular leukomalacia, hypoxic-ischemic encephalopathy, or malformations disrupt these pathways, leading to motor deficits. Advanced imaging techniques such as diffusion and functional magnetic resonance imaging (MRI) reveal altered connectivity patterns in CP, offering insights into its pathophysiology and aiding diagnosis. Studies have highlighted the variability of clinical presentations in CP and the correlation with specific brain regions affected. Deep brain stimulation and repetitive transcranial magnetic stimulation targeting the thalamus emerge as promising therapeutic opportunities to restore motor function in CP by addressing pathway disruptions. Conclusion: This review provides a comprehensive overview of motor pathways in CP, emphasizing the role of the thalamus and cortical connectivity in motor impairments. Understanding this complex connectivity provides an avenue for optimum and targeted therapeutic interventions to improve outcomes for individuals with CP.